Cultural Themes in Senior High School English Textbook: An Indonesian Context - ’Adzima, Rohmatul; Rochsantiningsih, Dewi; Suparno, Suparno (ICONELT, 2022)
Textbooks are still considered as the most popular learning tool in school education. Since language and culture are inextricable, teachers are now challenged in defining the best textbook that enables students, especially who are in senior high school learn both the language and the culture. To know what cultural content is represented in the textbook it is necessary to analyse its content in the form of cultural themes. This content analysis research aimed to investigate the stated cultural themes of English textbook at senior high school learning in Indonesia. The researcher collected the data through a textbook analysis checklist made based on the criteria of cultural themes proposed by Chen. The results showed that some parts of the book have been engaging culture in small “c” and big “C”. However, the amount is in a small number. In order to enrich cultural learning, students need more cultural themes of small “c” and big “C” to develop students’ cultural knowledge and competence. Knowledge about cultures will build students’ cultural competence and awareness. Thus, the inclusion of cultural should be the concern for the material developer of English textbook and English educators in the level of senior high school, especially in Indonesia.